2002
DOI: 10.2214/ajr.179.4.1790881
|View full text |Cite
|
Sign up to set email alerts
|

Using the World Health Organization Classification of Thymic Epithelial Neoplasms to Describe CT Findings

Abstract: Smooth contours and a round shape are most suggestive of type A thymic epithelial tumor, whereas irregular contours are most suggestive of type C tumor. Calcification is suggestive of type B tumors. CT is of limited value, however, in differentiating type AB, B1, B2, and B3 tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
101
1
20

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 26 publications
15
101
1
20
Order By: Relevance
“…If a needle biopsy is not possible or is non-diagnostic, several invasive surgical methods can be utilized for further diagnostic evaluation [1]. 18 F-FDG PET/ CT scanning may be a noninvasive method of predicting WHO histological subtypes and invasiveness of thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If a needle biopsy is not possible or is non-diagnostic, several invasive surgical methods can be utilized for further diagnostic evaluation [1]. 18 F-FDG PET/ CT scanning may be a noninvasive method of predicting WHO histological subtypes and invasiveness of thymic epithelial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the application of visual uptake grading has not been reported previously in thymic epithelial tumors; thus, our results are the first to show a significant difference on 18 F-FDG PET/CT between less-and more-invasive thymomas, not merely between thymic carcinomas and thymomas, even though visual grading is more simple than measuring SUVs. Sung et al [4] reported that homogeneous 18 F-FDG uptake pattern was observed more frequently in thymic carcinomas than in high-risk or low-risk thymomas. However, in our study an increasing tendency of heterogeneous 18 F-FDG uptake pattern was seen in the order: less-invasive to more-invasive thymoma to thymic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations